Health literacy and critical lecture as key elements to detect and reply to nutrition misinformation on social media: analysis between Spanish healthcare professionals - Segado-Fernández, Sergio; Lozano-Estevan, María del Carmen; Jiménez-Gómez, Beatriz; Ruiz-Núñez, Carlos; Jiménez-Hidalgo, Pedro Jesús; Fernández-Quijano, Invención; González-Rodríguez, Liliana G.; Santillán-García, Azucena; Herrera-Peco, Iván (MDPI, 2022)
Health misinformation about nutrition and other health aspects on social media is a current public health concern. Healthcare professionals play an essential role in efforts to detect and correct it. The present study focuses on analyzing the use of competencies associated with training in methodology, health literacy, and critical lecture in order to detect sources of health misinformation that use scientific articles to support their false information. A qualitative study was conducted between 15 and 30 January 2022, wherein the participants were recruited from active users from a nutrition conversation on Twitter, diets, and cancer and defined themselves as healthcare professionals. This study demonstrates that health literacy and critical lecture competencies allow for the detection of more misinformation messages and are associated with a high rate of responses to users that spread the misinformation messages. Finally, this study proposes the necessity of developing actions to improve health literacy and critical lecture competencies between healthcare professionals. However, in order to achieve this, health authorities must develop strategies to psychologically support those healthcare professionals faced with bullying as a result of their activity on social media debunking health hoaxes.
Keywords: Nutrición; Redes sociales; Educación sanitaria; Detection; Health misinformation; Healthcare professionals; Public health; Social media